Kajian Pustaka: Potensi Hypnosis untuk Mengurangi Nyeri pada Pasien yang Mendapatkan Perawatan Gigi dan Mulut - Eko Mulyadi (Fakultas Kedokteran Gigi Universitas Jember, 2021)
The purpose of this literature review is to find out whether hypnosis can be used to reduce pain in patients receiving dental and oral care. Hypnosis has been used to treat acute and chronic pain, anxiety, and other positive benefits before, during and after surgery. However, in the field, the use of hypnosis is still little used and even many who doubt its effectiveness. We reviewed articles in English using keywords: hypnosis, pain, anesthesia, dental, procedure with a time span from 1846 to 2019, with 20 selected articles on google scholars, pubmed, science direct, and the national library portal of the republic of Indonesia (PNRI). , Mesmerism hypnosis and Ericsonian hypnosis have been used for anesthesia for a long time before chemical anesthesia was discovered, the use of chemical anesthesia makes hypnosis no longer used as the main anesthetic in surgery, but in certain cases such as patients with multiple chemical sensitivity or patients with contraindications for general anesthesia, hypnosis still used as the primary anesthetic in surgery, currently hypnosis is widely used in perioperative surgery. The use of hypnosis with chemical anesthetics can increase the benefits and there are no reported side effects. Conclusion: hypnosis can be used as primary anesthesia, especially in certain cases, it needs well-designed research such as randomized control trials on the use of hypnosis with chemical anesthetics, both perioperatively and intraoperatively to obtain clearer and consistent scientific information about hypnosis and chemical anesthetics.